1993
DOI: 10.1002/jcb.240530109
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of endothelial cell proliferation, adhesion, and motility by recombinant heparin‐binding domain and synthetic peptides from the type I repeats of thrombospondin

Abstract: Thrombospondin is an inhibitor of angiogenesis that modulates endothelial cell adhesion, proliferation, and motility. Synthetic peptides from the second type I repeat of human thrombospondin containing the consensus sequence-Trp-Ser-Pro-Trp- and a recombinant heparin binding fragment from the amino-terminus of thrombospondin mimic several of the activities of the intact protein. The peptides and heparin-binding domain promote endothelial cell adhesion, inhibit endothelial cell chemotaxis to basic fibroblast gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 34 publications
4
103
1
1
Order By: Relevance
“…TSP1 Inhibits NO-Stimulated Proliferation. TSP1 inhibits proliferation of endothelial cells, with reported IC 50 values of 5-70 nM, depending on the growth medium (36)(37)(38). Consistent with those studies, 22 nM TSP1 was required to significantly inhibit BAEC proliferation stimulated by serum in the absence of NO donor, but proliferation stimulated by 10 M DETA͞NO was inhibited by 50% at Ͻ22 pM TSP1 (Fig.…”
Section: No Is a Biphasic Modulator Of Endothelial Cell Proliferationsupporting
confidence: 84%
See 1 more Smart Citation
“…TSP1 Inhibits NO-Stimulated Proliferation. TSP1 inhibits proliferation of endothelial cells, with reported IC 50 values of 5-70 nM, depending on the growth medium (36)(37)(38). Consistent with those studies, 22 nM TSP1 was required to significantly inhibit BAEC proliferation stimulated by serum in the absence of NO donor, but proliferation stimulated by 10 M DETA͞NO was inhibited by 50% at Ͻ22 pM TSP1 (Fig.…”
Section: No Is a Biphasic Modulator Of Endothelial Cell Proliferationsupporting
confidence: 84%
“…A comparable potency was reported for TSP1 to inhibit endothelial cell chemotaxis stimulated by fibroblast growth factor 2 (FGF2) (IC 50 ϭ 22 pM) (36), but others obtained a much higher IC 50 of 700 pM (43). In contrast, 50% inhibition of endothelial cell proliferation stimulated by FGF2 typically requires 5-70 nM TSP1 (36)(37)(38). TSP1 inhibits endothelial cell adhesion, as assessed by focal adhesion disruption, with a reported IC 50 of 2-4 nM (44).…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have revealed that treatment of endothelial cells with TN or other related proteins such as SPARC and thrombospondin (TSP) result in a diminished number of focal adhesions (MurphyUllrich and Hook, 1989;Vrucinic-Filipi andChiquet-Ehrismann, 1993, Murphy-Ullrich et al, 1991). Furthermore, these interactions might also result in modulation of adhesive contacts and cellular receptivity to motility factors leading to reorganization of the actin cytoskeleton (Goldblum et al, 1994, Vogel et al, 1993, Rosen et al, 1990. The profound reorganization of HUVECs on A375SM matrix expressing TN and the role of TN in endothelium adhesion supports the hypothesis that TN might mediate tumor cell-endothelial cell interactions.…”
Section: Discussionmentioning
confidence: 71%
“…Recombinant fragments and GST or T7 fusion proteins expressing fragments of TSP1 were prepared as described (15,19,20). Synthetic peptides containing TSP1 sequences were prepared as described previously (2,14,(21)(22)(23)(24).…”
Section: Methodsmentioning
confidence: 99%
“…Peptides from the type 1 repeats and procollagen domains that bind to CD36 inhibit endothelial cell motility (12,13). Heparin-binding peptides from the type I repeats promote cell adhesion and chemotaxis (14) but also inhibit growth, motility, and survival of endothelial cells (8,15). The RFK sequence in the second type 1 repeat activates latent transforming growth factor-␤1 (16).…”
Section: Thrombospondin-1 (Tsp1)mentioning
confidence: 99%